History of Oropharyngeal Organs and Swallowing - Cumhur Ertekin; İbrahim Aydoğdu (Türk Nöroloji Dergisi, 2023)
This review aims to present a brief historical perspective of the clinical development of swallowing since ancient times. It also highlights the discovery of the functional meaning of the oropharyngeal organs. These historical developments are enriched with some anecdotal details.